EFEKTIFITAS PENERAPAN PROJECT BASED LEARNING BERBANTUAN WEB 2.0 TOOLS DAN DEMING CYCLE PADA MATAKULIAH PEMECAHAN MASALAH MATEMATIKA - Nohel Yemima (Universitas Kristen Satya Wacana, 2015)
This is a Quasi Experimental research which aimed to know the effectiveness of implementing Project Based Learning (PBL) with assistance of Web 2.0 tools and Deming Cycle towards the learning achievement in Mathematics Problem Soving Course of undergraduate students in Primary School Teacher Education Program in Satya Wacana Christian Univerisity (PGSD, UKSW). This research included 52 students which were devided into two classes consist of 26 students. In the experimental group, the treatment were given by implementing a PBL with Web 2.0 tools and Deming Cycle whereas in control group, PBL was implemented but without the use of Web 2.0 tools and Deming Cycle. The T-Test anylisis showed that the experimental group had the significant increasing of learning achievement compare to the control group. As the result, in the third term of 2013/2014 accademic year, it is effective to improve students learning achievement in Mathematics Problem Solving Course by implementing PBL with the assistance of Web 2.0 tools and Deming Cylce.